An Audit of the Use of a Ligature Assessment Tool in the Reporting of Ligature Incidents in a Regional Women’s Medium Secure Unit - Thomas Teall; Bijal Arvind Sangoi; Zakaria Saidani (BJPsych Open)
Aims: Ligature incidents in inpatient psychiatric settings represent a high-risk form of self-harm behaviour. Of all deaths that occur on psychiatric wards, 75% are caused by hanging or strangulation with a ligature. Accurate assessment and documentation of ligature incidents is essential for a comprehensive understanding of these complex incidents. A Ligature Assessment Tool was developed (Panchal et al, 2022) to improve and standardise the reporting of these incidents. Use of the tool provides a detailed source of information for the multi-disciplinary team, many of whom won’t have observed the incident first hand. These detailed reports can subsequently inform the care planning for individual patients.